Prostate-Specific Antigen Doubling Time as a Predictor of Gleason Grade in Prostate Cancer - Nowroozi, Mohammad Reza; Zeighami, Shahryar Zeighami; Ayati, Mohsen; Jamshidian, Hassan; Ranjbaran, Ali Reza; Moradi, Asaad; Afsar, Firuzeh (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: Our aim was to evaluate the value of serum prostate-specific antigen doubling time (PSADT) to identify patients with high-grade prostate cancer who require more aggressive therapy from those with low-grade cancer. Materials and Methods: Of 460 patients with extended 12-core transrectal ultrasonography-guided biopsy of the prostate, 59 with confirmed prostate cancer were selected. They had not received any previous treatment for prostate cancer and had at least 2 consecutive serum PSA tests with a rising trend. The PSADT was calculated in patients with 2 serum PSA levels measured with an interval more than 3 months. Results: Of 59 patients with prostate cancer, 35 (59.3%) had low-grade and 24 (40.7%) had high-grade tumors. There was no difference in age between the two groups. The median PSADT in patients with high-grade and low-grade tumors were 12.70 Â± 2.66 months (range, 0.7 to 44.8 months) and 25.00 Â± 22.50 months (range, 1.65 to 41.2 months; P = .001). A total of 21 patients with high-grade tumors (87.5%) had a PSADT less than 12 months, while only 9 of those with low-grade tumors (25.7%) had a PSADT less than 12 months. A PSADT cutoff of 12 months provided a sensitivity of 74% and a specificity of 87% for differentiation of high-grade from low-grade cancers. Conclusion: We showed that men with a short PSADT (< 12 months) were at a higher risk of harboring a high-grade prostate cancer. Our data suggests PSADT to identify patients with high-grade tumors who require more aggressive therapy.